2014
DOI: 10.1902/jop.2013.130066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Enzymes Activity and Malondialdehyde Levels in Patients With Chronic Periodontitis and Diabetes Mellitus

Abstract: This study favors the role of oxidative stress in both diabetes and periodontitis. It shows that the compensatory mechanism of the body is partially collapsed because of excessive production of free radicals during periodontitis and is not able to cope with increased free radical generation attributable to diabetes, thereby worsening the situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
7
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 42 publications
12
83
7
3
Order By: Relevance
“…The results of the present study agree with literature relating high levels of salivary antioxidants (SAT) to a possible periodontal inflammatory condition. In response to oxidative stress, antioxidant enzymes appeared upregulated in inflamed periodontal tissues [27,28]. The longitudinal analysis of this trial showed a normalization of SAT values three months after non-surgical periodontal treatment.…”
Section: Number Of Dm-2 38mentioning
confidence: 62%
“…The results of the present study agree with literature relating high levels of salivary antioxidants (SAT) to a possible periodontal inflammatory condition. In response to oxidative stress, antioxidant enzymes appeared upregulated in inflamed periodontal tissues [27,28]. The longitudinal analysis of this trial showed a normalization of SAT values three months after non-surgical periodontal treatment.…”
Section: Number Of Dm-2 38mentioning
confidence: 62%
“…Our results are in accordance to studies by Singh et al, (30) they used SOD ELISA kit and found median salivary SOD levels to be 10.95 U/ml in chronic periodontitis subjects as compared to 21.66 U/ml in healthy controls. Trivedi et al, (48) reported lowest salivary SOD levels in diabetic, periodontally healthy subjects (13.45+2.80U/ml) and highest in healthy controls (29.64+6.98U/ml) however, SOD mean values in chronic periodontitis patients fell in between them (19.93+12.05 U/ml). On the contrary Wei et al, (29) revealed higher salivary SOD levels in CP patients (216.4+36.78U/mg protein) than controls (174.9+21.07) which they attributed to an overall increased oxidant status of CP group.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that hypercholesterolaemia increases the blood level malondialdehyde (MDA), one of the lipid peroxidation products. In addition, the level of reactive oxygen species (ROS), produced by polymorphonuclear leucocytes also increases along with decrease in activities of many tissue antioxidant enzymes [2].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds include antioxidative enzymes, such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione reductase (GR) and non-enzymatic antioxidants, such as glutathione (GSH), vitamin C and vitamin E [2]. The efficiency of this defense system is apparently weakened in hypercholesterolaemia condition resulting in ineffective scavenging of free radicals which may lead to tissue damages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation